Developing a risk score to predict mortality in the first year after implantable cardioverter defibrillator implantation: Data from the Israeli ICD Registry. (25th September 2018) - Nevzorov, Roman; Goldenberg, Ilan; Konstantino, Yuval; Golovchiner, Gregory; Strasberg, Boris; Souleiman, Mahmoud; Khalameizer, Vladimir; Ben‐Zvi, Shlomit; Sela, Ron; Rosenheck, Shimon; Freedberg, Nahum A.; Geist, Michael; et al.
Abstract: Introduction: Life expectancy of less than 1 year is usually a contraindication for implantable cardioverter defibrillator (ICD) implantation. The aim was to identify patients at risk of death during the first year after implantation. Methods and Results: Data were derived from a prospective Israeli ICD Registry. Two groups of patients were compared, those who died and those who were alive 1 year after ICD implantation. Factors associated with 1‐year mortality were identified on a derivation cohort. A risk score was established and validated. A total of 2617 patients have completed 1 year of follow‐up after ICD or cardiac resynchronization therapy defibrillator (CRT‐D) implantation. Age greater than 75 years (hazard ratio [HR], 2.7; 95% confidence interval [95% CI], 1.6 to 4.4), atrial fibrillation (AF; HR, 1.9; 95% CI, 1.12 to 3.17), chronic lung disease (HR, 2.0; 95% CI, 1.1 to 3.76), anemia (HR, 2.3; 95% CI, 1.3 to 3.93) and chronic renal failure (CRF; HR, 3.4; 95% CI, 1.74 to 6.6) were independent risk factors for 1‐year mortality. We propose a simple AAACC ("triple A double C") score for prediction of 1‐year mortality after ICD implantation: Age greater than 75 years (3 points(pts)), anemia (2 pts), AF (1 pt), CRF (3 pts) and chronic lung disease (1 pt). Mortality risk increased with rising number of points (from 1% with 0 pts to 12.5% with >4 pts). The risk score was evaluated with receiver operating characteristic curve and the area under the curve of the validation curve is 0.71 (95% CI, 0.66 to 0.76). Conclusions: Age greater than 75, AF, chronic lung disease, anemia, and CRF were independent risk factors for 1‐year mortality. AAACC risk score identifies patients at high risk of death during 1 year after ICD implantation.